Seppuku: Kematian Terhormat dalam Tradisi Jepang - Titiek Suliyati (Diponegoro University, 2019)
In modern times, the era after the Meiji Restoration, seppuku gradually disappeared when the samurai group was abolished. Although in Japan there are still people who commit seppuku and harakiri but the motivation, implementation methods and objectives are different from seppuku and harakiri in the era before the Meiji restoration. The changes and dynamics of Japanese society in conducting seppuku and harakiri are very interesting to study. The purpose of writing this article is to find out whether there is a correlation between seppuku tradition and the number of suicides in Japan at this time. To explore this correlation, the writing of this article uses a qualitative method with a historical approach. The stages of historical research begin with data collection (heuristics), source criticism, interpretation and writing of research results in the form of articles. The analysis was performed using qualitative methods which include data reduction, data presentation, and concluding. The results of the study concluded that there is no strong correlation between seppuku traditions in the past with suicide (jisatsu) that many Japanese do today. There is a difference in purpose, motivation and background in their suicide.